European Cooperative Acute Stroke Study-4: Extending the time for thrombolysis in emergency neurological deficits ECASS-4: ExTEND. Issue 2 (February 2016) - Amiri, Hemasse; Bluhmki, Erich; Bendszus, Martin; Eschenfelder, Christoph C; Donnan, Geoffrey A; Leys, Didier; Molina, Carlos; Ringleb, Peter A; Schellinger, Peter D; Schwab, Stefan; Toni, Danilo; Wahlgren, Nils; et al.
Rationale and hypothesis: Thrombolytic therapy with recombinant tissue plasminogen activator (rt-PA) is an effective and approved therapy for acute ischemic stroke within 4.5 h of onset except for USA, Canada, Croatia, and Moldovia with a current 3 h label. We hypothesized that ischemic stroke patients selected with significant penumbral mismatch on magnetic resonance imaging (MRI) at 4.5–9 h after onset of stroke will have improved clinical outcomes when given intravenous rt-PA (alteplase) compared to placebo. Study design: ECASS-4: ExTEND is an investigator driven, phase 3, randomized, multi-center, double-blind, placebo-controlled study. Ischemic stroke patients presenting within 4.5 and 9 h of stroke onset, who fulfil clinical requirements (National Institutes of Health Stroke Score (NIHSS) 4–26 and pre-stroke modified Rankin Scale (mRS) 0–1) will undergo MRI. Patients who meet imaging criteria (infarct core volume <100 ml, perfusion lesion: infarct core mismatch ratio >1.2 and perfusion lesion minimum volume of 20 ml) additionally will be randomized to either rt-PA or placebo. Study outcome: The primary outcome measure will be the categorical shift in the mRS at day 90. Clinical secondary outcomes will be disability at day 90 dichotomized as favorable outcome mRS 0–1 at day 90. Tertiary endpoints include reduction in the NIHSS by 11 or more points or reaching 0–1 at day 90, reperfusion and recanalization at 24 h post stroke as well as depression, life quality, and cognitive impairment at day 90. Safety endpoints will include symptomatic intracranial hemorrhage (ICH) and death.